(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Ñ ABSTRACT Ñ The study aimed to determine the most important requirements that prevent the outputs of applied technical education from being optimally invested in order to meet the labor market need of the applied human resource, which is supposed to be qualified and trained to directly engage in the labor market, and are represented in two important aspects, the first aspect is the harmonization between The nature of education systems and higher education on the one hand for the sake of the labor market, and the second is the availability of financial financing, which is the most important factor to influence the preparation of applied human outputs capable of engaging in the work field without the need to seek foreign assistance on the other hand, The researcher relied on both the deductive approach as a general approach to research and the descriptive-analytical method, and distributed a questionnaire to (405) members of the teaching staff and the research community in the Applied College at Tishreen University, 399 questionnaires were retrieved, of which (374) were usable. Then, the primary and secondary data obtained were analyzed; Using statistical analysis software (SPSS) The researcher reached conclusions which showed the weakness of the educational education systems represented by educational curricula and study plans in comparison with the curricula and study plans for applied education at the university level, which reflected negatively on the outputs in technical education due to the lack of modern information matching the needs of these markets according to the local and global economic growth and development. The study; And the lack of financial interest in applied education, as a result of funding being limited only to government resources (allocations), and the public and private institutions sector not contributing to financing in cash or in kind.